THE INFLUENCE OF THE INTERNET ON THE STUDENTS’ ACHIEVEMENT IN WRITING ANALYTICAL EXPOSITION TEXT - Rafika Purba (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2016)
This research deals with the writing skill. The problem of the study is there the significant influence of the internet on the students’ ability in writing analytical exposition text. the objective of the study is: To know is there the significant influence of the internet on the students’ ability in writing analytical exposition text. Related to the research problems, the writer used writing test as an instrument. The finding of this study has proven that internet can improve the students writing ability. It can be seen from the improvement of the students’ score. The students’ average score in the (pre-test) was 58 for experimental group and 56 for control group. After the implementation of internet as media, it became 78 for experimental group. In other word, 87 already achieved scores greater than 56 as the criterion of success determined. As result internet can influence students’ achievement in writing skill. The main finding of this study shown that the student who used internet- based tasks had a good level of writing than who did not use internet in their learning process. The effect of the study indicated, interned- based writing tasks had a significant effect on students’ achievement in writing. Keywords: writing skill, writing text, analytical exposition text, interned- based writing, the influence of internet